2013
DOI: 10.1111/febs.12268
|View full text |Cite
|
Sign up to set email alerts
|

Finding novel pharmaceuticals in the systems biology era using multiple effective drug targets, phenotypic screening and knowledge of transporters: where drug discovery went wrong and how to fix it

Abstract: Despite the sequencing of the human genome, the rate of innovative and successful drug discovery in the pharmaceutical industry has continued to decrease. Leaving aside regulatory matters, the fundamental and interlinked intellectual issues proposed to be largely responsible for this are: (a) the move from 'function-first' to 'target-first' methods of screening and drug discovery; (b) the belief that successful drugs should and do interact solely with single, individual targets, despite natural evolution's sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 424 publications
(454 reference statements)
0
100
0
4
Order By: Relevance
“…The hypothesis-led approach is the one I have taken here, and the many publications analysed in our various papers on this topic (e.g., [5,6,[12][13][14][15][16][17]19]) provide data and evidence that, perhaps surprisingly, or even shockingly, thus far fail to falsify the hypothesis that, for the transport of pharmaceutical drugs across intact biological membranes, phospholipid bilayer diffusion is negligible. Many opportunities for novel approaches exist (Box 1), however, and I look forward to further tests of these consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis-led approach is the one I have taken here, and the many publications analysed in our various papers on this topic (e.g., [5,6,[12][13][14][15][16][17]19]) provide data and evidence that, perhaps surprisingly, or even shockingly, thus far fail to falsify the hypothesis that, for the transport of pharmaceutical drugs across intact biological membranes, phospholipid bilayer diffusion is negligible. Many opportunities for novel approaches exist (Box 1), however, and I look forward to further tests of these consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, these transporters are taken to be there not specifically for the benefits of pharmaceuticals companies but for the purposes of intermediary metabolism. To this end we have summarised the evidence for the dominance of transporter-mediated uptake in several review and experimental articles [5,6,[12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Direct effect by linking of anesthetics to proteins and indirect action on the lipid membrane properties are the two hypotheses in conflict’.” Counter: this is an example of highly selective reporting; the paper cited is not even about biological membranes, and the apodosis of the title of the paper (“looking for a lipid-mediated mechanism of anesthesia”) implies an agenda that seeks to pre-judge the answer. We have discussed the extensive literature of general anesthetics many times (Dobson and Kell, 2008; Dobson et al, 2009a,b; Kell and Dobson, 2009; Kell et al, 2011, 2013; Kell, 2013; Kell and Goodacre, 2014), and the available data show clearly the involvement of a variety of proteins such as GABA A receptors (Mihic et al, 1997; Jurd et al, 2003; Bonin and Orser, 2008), potassium channels (Patel et al, 1999; Thompson and Wafford, 2001; Franks and Honoré, 2004; Gruss et al, 2004; Heurteaux et al, 2004; Grasshoff et al, 2006; Andres-Enguix et al, 2007; Bertaccini and Trudell, 2012), glycine receptors (Mihic et al, 1997; Lobo and Harris, 2005; Dickinson et al, 2007; Bertaccini et al, 2010), and NMDA receptors (Sanders et al, 2003; Dickinson et al, 2007; Dickinson and Franks, 2010). The sites of interaction of general anesthetics with a number of their target membrane proteins are now known with molecular resolution, including their variation in mutant forms of the same proteins (that correlate with changes in anesthetics potency—see e.g., Nury et al, 2011; Stansfeld and Sansom, 2011).…”
Section: Intellectual Challenges Around Bilayer Lipoidal Permeabilitymentioning
confidence: 99%
“…As part of an ongoing discussion of the importance of transporters in drug distribution that we (Dobson and Kell, 2008; Dobson et al, 2009a,b; Kell and Dobson, 2009; Kell et al, 2011, 2013; Lanthaler et al, 2011; Kell, 2013; Kell and Goodacre, 2014) and others (e.g., Sai and Tsuji, 2004; Shitara et al, 2006; Anderson and Thwaites, 2010; Franke et al, 2010; Giacomini et al, 2010, 2013; Lai et al, 2010; Burckhardt and Burckhardt, 2011; Fromm and Kim, 2011; König, 2011; Mruk et al, 2011; Nies et al, 2011; Thompson, 2011; Tirona, 2011; Zolk and Fromm, 2011; Degorter et al, 2012; Mandery et al, 2012; Riedmaier et al, 2012; Sprowl et al, 2012; Chu et al, 2013b; Estudante et al, 2013; Giacomini and Huang, 2013; Hagenbuch and Stieger, 2013; König et al, 2013; Schlessinger et al, 2013a,b; Tamai and Nakanishi, 2013; Lai and Hsiao, 2014; Sprowl and Sparreboom, 2014) have been highlighting, Smith and colleagues recently published a review (Smith et al, 2014) that claims that the hypothesis that drugs are usually transported into cells via protein carriers is “not a sound scientific principle and lacks experimental evidence.” Smith et al (2014) set out their arguments in considerable detail, and this allows us, in the present publication, to present a contrary view and rehearse the core arguments that pertain to the mechanism(s) of drug and xenobiotic transport across biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, a highly specific treatment should be better tolerated due to an absence of off-target side effects. Unfortunately, practice has shown that there is a poor correlation between in vitro drug effects and in vivo efficacy with target-driven approximations [2,3]. Our increasing understanding of the multiple interacting feedback mechanisms operating within the cell has led to the realization that polypharmacology (the interaction of a single drug on multiple targets or the use of multiple drugs on multiple targets) will be necessary to treat the majority of non-monogenic disorders [4][5][6][7].…”
Section: Opinionmentioning
confidence: 99%